(untitled) (Conference on English Language Teaching, 2023)
Teaching reading poses a formidable challenge for EFL learners due to the Indonesian educational system’s sole emphasis on comprehension and vocabulary exercises, neglecting the cultivation of critical thinking skills necessary for engaging with the text. The objective is to assess students’ proficiency in various tenses and their corresponding reading comprehension abilities. This research focuses on a distinct group of 8 students who are distributed among three classes. To obtain a representative sample, the researchers randomly chose 8 students from each class, resulting in total of 8 participants. These students encountered challenges primarily in the areas of grammar, listening, and writing. Based on this scenario, our objective is to establish a connection between the mastery of tenses and the ability to comprehend functional texts. From all the actions we undertook, obtained remarkable outcomes that enhanced their skills. There exists connection among them, indicating the robustness of the three variables. The research findings lead to the conclusion that a positive correlation exists between students’ proficiency in tenses and their comprehension of reading functional texts. Put differently, as students’ mastery of tenses improves, so does their achievement in comprehending reading functional texts.